Where in the wild - Bishop, Poppy (Tiger Tales, 2018)
"Animals are found in every environment around the world from the rain forest to the savanna to the desert. Some creatures, like butterflies and foxes, can survive in many different habitats. Lyrical text and stunning illustrations bring to life the inhabitants of these unique environments"--Jacket.